IoT Control System for Switch and Socket - Ahmad Naqeeb Rosnan,; Maizul Ishak, (Progress in Engineering Application and Technology, 2024)
This project aims to develop a Smart IoT Control System for Switches and Sockets, driven by the growing demand for intelligent and automated control in residential and commercial settings. Utilizing IoT technology, the system enables remote operation and monitoring through a user-friendly interface. The initiative involves a literature analysis, hardware selection, circuit design, and software development. Rigorous testing ensures system dependability, functionality, and adherence to objectives, while addressing ethical concerns. The goal is to create an efficient, user-friendly interface for remote control and monitoring, leading to improved energy efficiency and enhanced user experience.